ANALISIS PENGARUH PRODUKSI ROKOK TEMBAKAU TERHADAP PENERIMAAN CHT: STUDI KASUS JAWA BARAT 2022-2024 - Qunaitah; Naufal Rasyid, Fakhri; Dania Lestari, Nada; Ervani, Eva (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
This research aims to analyze the correlation between the production of legal cigarettes, consisting of machine-made kretek cigarettes (SKM), hand-rolled kretek cigarettes (SKT), and machine-made white cigarettes (SPM), and the effectiveness of crackdown on illegal cigarettes on tobacco product excise (CHT) revenues in West Java in the period January 2022 to October 2024. Using a quantitative approach with multiple linear regression methods based on time series data from the Directorate General of Customs and Excise (DJBC) West Java, the research results show that increasing the production volume of SKM, SKT, and SPM is positively and significantly related to CHT acceptance